TINGKAT PENGETAHUAN IBU HAMIL PRIMIGRAVIDA TRIMESTER II DAN III TENTANG TANDA-TANDA BAHAYA DALAM KEHAMILAN DI KLINIK ROMANA TANJUNG ANOM TAHUN 2017 - MERLINA SINABARIBA (LP2MTBM MAKARIOZ, 2019)
The danger sign in pregnancy is a sign that indicates a danger that can occur during pregnancy which if not detected will cause the death of mother and fetus. This research is descriptive by using a cross sectional design with a population of 43 respondents and the total amount of population are sampled, the technique that is used for the sample is consecutive sampling. Data collection used in this study is primary data collection obtained by distributing questionnaires to each respondent. Several factors that influence the knowledge level of mothers are age, sources of information, education, and occupation. The results showed that out of 43 respondents, there were 20 people (46.51%) who were knowledgeable enough, 13 respondents (30.23%) who were good knowledge, and 10 respondents (23.26%) who were less knowledgeable. Knowledge of respondents based on the most age is 19-23 years old with 18 respondents (41.86%), and the least knowledge at the age of 29-33 years old with 12 respondents (27.91%). Knowledge of respondents based on the most sources of information was 17 health workers (39.53%) and the least was electronic media with 6 respondents (13.95%). Knowledge of respondents based on the most education is high school as many as 27 respondents (62.79%) and the least knowledge of Higher Education is 2 respondents (4.65%). The most occupation who has more knowledge is housewives as many as 27 respondents (55.81%) and the least is self-employment as many as 6 respondents (9.30%). Based on the results of the study are expected for pregnant women to increase their knowledge of danger signs in pregnancy through health workers, print media, and electronic media.